2015
DOI: 10.1044/2015_jslhr-l-14-0003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Verb Familiarity on Finiteness Marking in Children With Specific Language Impairment

Abstract: Purpose Children with Specific Language Impairment (SLI) have known deficits in the verb lexicon and finiteness marking. This study investigated a potential relationship between these two variables in children with SLI and two control groups considering predictions from two different theoretical perspectives, morphosyntactic vs morphophonological. Method Children with SLI, age-equivalent (AE) and language-equivalent (LE) control children (N = 59) completed an experimental sentence imitation task that generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…We hypothesized, however, that the morphosyntactic deficit in children with SLI would exacerbate the noun-verb dissociation because verbs carry syntactic information (e.g., Andreu et al, 2012;Hennessey et al, 2010;Kan & Windsor, 2010;Sheng & McGregor, 2010). This is consistent with hypotheses that limited verb representations, revealed through poor performance on lexical tasks, may be one of the problems underlying weak finiteness marking in children with SLI (e.g., Abel, Rice, & Bontempo, 2015;Hoover et al, 2012). Regardless of the outcomes, the results will help us understand how children simultaneously consider phonological and syntactic information during word recognition and whether isolated verb recognition emerges as an area of lexical difficulty in children with SLI.…”
Section: Current Studysupporting
confidence: 63%
“…We hypothesized, however, that the morphosyntactic deficit in children with SLI would exacerbate the noun-verb dissociation because verbs carry syntactic information (e.g., Andreu et al, 2012;Hennessey et al, 2010;Kan & Windsor, 2010;Sheng & McGregor, 2010). This is consistent with hypotheses that limited verb representations, revealed through poor performance on lexical tasks, may be one of the problems underlying weak finiteness marking in children with SLI (e.g., Abel, Rice, & Bontempo, 2015;Hoover et al, 2012). Regardless of the outcomes, the results will help us understand how children simultaneously consider phonological and syntactic information during word recognition and whether isolated verb recognition emerges as an area of lexical difficulty in children with SLI.…”
Section: Current Studysupporting
confidence: 63%
“…Examples of these types of errors might include omissions or substitutions of content words, such as nouns and verbs, and ungrammatical alterations of words within clauses (e.g., new rap a song for the target a new rap song). Previous sentence recall studies have shown that children with SLI produce fewer grammatical recalls than controls, making errors they don't always produce in conversation and with errors spanning content words, function words, and inflections (Frizelle & Fletcher, 2014b;Riches, 2012;Seeff-Gabriel et al, 2010;Smolík & Várnů, 2014; but see also Abel, Rice, & Bontempo, 2015, who found similar proportions of grammatical recalls for children with SLI and controls when stimuli involved simple syntax). The current study was designed to further test this hypothesis in the context of AAE and SWE.…”
Section: Rate-based Differences Between Aae Swe and The Grammaticalmentioning
confidence: 93%
“…Sentence imitation tasks are an assessment method used to elicit specific grammatical structures. Sentence imitation tasks are used in the child language disorders literature, given their ease in administration and effectiveness in identifying problematic structures (Abel, Rice, & Bontempo, 2015;Hoover, Storkel, & Rice, 2012). As compared to language sample analysis, sentence imitation tasks afford more efficiency in eliciting multiple instances of targeted grammatical morphemes.…”
Section: Assessment Methods and Contextmentioning
confidence: 99%